PENGEMBANGAN PROGRAM BIMBINGAN & KONSELING UNTUK MENINGKATKAN KARAKTER KEMAMPUAN INDIVIDU PESERTA DIDIK DI MADRASAH ALIYAH NEGERI PURWAKARTA - Farah Wahyuni; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to develop a guidance and counseling program to improve the academic intelligence of class X MAN Purwakarta students. This is based on initial findings on the results of a need assessment using the grit scale instrument which shows that the academic grit aspect is still low, where students who have low academic grit tend to disrupt the development of learning in class. Methods This study used a quasi-experimental research design approach with one group pretest - posttest supplemented by descriptive analysis. The research subjects were students of class X Man Purwakarta. Data collection was carried out using pretest and posttest, observation, and student worksheets. The data collection technique used is simple random sampling using the grit instrument. Based on the Quasi Experiment One Group Pretest – Posttest research, the initial pretest results found a score of 47.5, a change from the pre-test score to the post-test score, where for the experimental class the average increased by 32.2 while for the control class it increased by 79.629. This shows that there are differences in treatment between the experimental class and the control class. This proved to be effective because it showed that most of the students had tough characteristics such as those aimed at students with high grit so that they could be said to have achieved as much as possible.